Does Periodontal Inflammation Affect Type 1 Diabetes in Childhood and Adolescence? A Meta-Analysis - Rapone, Biagio; Corsalini, Massimo; Converti, Ilaria; Loverro, Maria Teresa; Gnoni, Antonio; Trerotoli, Paolo; Ferrara, Elisabetta (Frontiers in Endocrinology, 2020)
The emergence of link between periodontal disease and diabetes has created conditions for analyzing new interdisciplinary approach making towards tackling oral health and systemic issues. As periodontal disease is a readily modifiable risk factor this association has potential clinical implications. The aim of this paper was systematically review the extant literature related to analytics data in order to identify the association between type I diabetes in childhood and adolescence with periodontal inflammation. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we conducted a database search between 2004 and 2019. A manual search of the literature was conducted as an additional phase of the search process, with the aim of identifying studies that were missed in the primary search. One hundred and thirty-nine records were screened and ten fulfilled the inclusion criteria. Most studies were of moderate methodological quality. Outcomes included assessments of diabetes and periodontal status. In diabetic populations, compared to healthy subjects, interindividual differences in periodontal status are reflected in higher severity of periodontal inflammation. The most reported barriers to evidence uptake were the intrinsic limits of cross-sectional report data and relevant research, and lack of timely research output. Based on the evidence presented within the literature, the aforementioned biomarkers correlate with poor periodontal status in type I diabetic patients. Whilst the corpus of the evidence suggests that there may be an association between periodontal status and type diabetes, study designs and methodological limitations hinder interpretation of the current research.